Ways of the world a global history with sources - Strayer, Robert W.; Nelson, Eric (Bedford/St. Martin's, 2016)
1. First peoples; first farmers: Most of history in a single chapter, to 4000 B.C.E. -- 2. First civilizations: Cities, states, and unequal societies, 3500 B.C.E.-600 B.C.E. -- 3. State and empire in Eurasia/North Africa, 600 B.C.E.-600 C.E. -- 4. Culture and religion in Eurasia/North Africa, 600 B.C.E.-600 C.E. -- 5. Society and inequality in Eurasia/North Africa, 600 B.C.D.-600 C.E. -- 6. Commonalities and variations: Africa, the Americas, and Pacific Oceania, 600 B.C.E.-1200 C.E. -- 7. Commerce and culture, 600-1450 -- 8. China and the world: East Asian connections, 600-1300 -- 9. The worlds of Islam: Afro-Eurasian connections, 600-1450 -- 10. The worlds of Christendom: contraction, expansion, and division, 600-1300 -- 11. Pastoral peoples on the global stage: the Mongol moment, 1200-1450 -- 12. The worlds of the Fifteenth century -- 13. Political transformations: empires and encounter, 1450-1750 -- 14. Economic transformations: commerce and consequence, 1450-1750 -- 15. Cultural transformations: religion and science, 1450-1750 -- 16. Atlantic revolutions, global echoes, 1750-1900 -- 17. Revolutions of Industrialization, 1750-1900 -- 18. Colonial encounters in Asia, Africa, and Oceania, 1750-1950 -- 19. Empires in collision: Europe, the Middle East, and East Asia, 1800-1900 -- 20. Collapse at the center: World War, Depression, and the rebalancing of global power, 1900-1970s -- 21. Revolution, socialism, and global conflict: the rise and fall of world Communism, 1917-present -- 22. The end of Empire: the global South on the global stage, 1900-present -- 23. Capitalism and culture: the acceleration of globalization, since 1945.